Urinary Tract Infection Management in Elderly People : Approach Beyond the Pills and Needles - Chowdhury, Abhijit; Ferdoush, Jannatul; Rahman, Mokhlesur; Das, Binayok; Sarker, Prasenjit (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
This review article focuses on critical analyses of the approach towards the management of older adults suffering from urinary tract infections. The article sheds light on the better scopes of management for these patients beyond the conventional treatment strategies to deal with the disease complexities with a goal to achieve patient satisfaction as well as fulfilling their psychosocial needs. Medline (1946) Scopus, Embase,CINAHL and PsycINFO were searched for articles published from 1980 to 2015 using the keywords Urinary Tract Infection, Older Adults, Elderly, Aged and Aged Care Facilities. The reference lists of the selected publications were also reviewed. Articles published only in English have been chosen. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 3-6